Gut Microbiome and Plasma Metabolome Signatures in Middle-Aged Mice With Cognitive Dysfunction Induced by Chronic Neuropathic Pain - Hua, Dongyu; Li, Shan; Li, Shiyong; Wang, Xuan; Wang, Yue; Xie, Zheng; Zhao, Yilin; Zhang, Jie; Luo, Ailin (Frontiers in Molecular Neuroscience, 2022)
Patients with chronic neuropathic pain (CNP) often complain about their terrible memory, especially the speed of information processing. Accumulating evidence suggests a possible link between gut microbiota and pain processing as well as cognitive function via the microbiota-gut-brain axis. This study aimed at exploring the fecal microbiome and plasma metabolites profiles in middle aged spared nerve injury (SNI) mice model with cognitive dysfunction induced by CNP. Hierarchical cluster analysis of performance in the Morris water maze test was used to classify SNI mice with cognitive dysfunction (CD) or without cognitive dysfunction (NCD) phenotype. 16S rRNA sequencing revealed a lower diversity of gut bacteria in SNI mice, and the increase of Actinobacteria, Proteus, and Bifidobacterium might contribute to the cognitive impairment in the CNP condition. The plasma metabolome analysis showed that the endocannabinoids system, disturbances of lipids and amino acids metabolism might be the dominant signatures of CD mice. Fecal microbiota transplantation of sham (not CD) group improved allodynia and cognitive performance in pseudo-germ-free mice via normalizing the mRNA expression of endocannabinoid receptors, including cn1r, cn2r, and ht1ra, reflecting the effects of gut bacteria on metabolic activity. Collectively, the findings of this study suggest modulation of gut microbiota and endocannabinoid signaling may serve as therapeutic targets for cognitive deficits in CNP patients.